Development of in vitro 3D brain models on laser fabricated scaffolds (Transactions on Additive Manufacturing Meets Medicine, 2021)
In this work, we present the design and implementation of a 3D scaffold platform that supports and promotes intricate neuronal network development. 3D scaffolds were produced by two-photon polymerization (2PP), a high-resolution 3D laser microstructuring technology, using the biocompatible and non-degradable photopolymer. Human iPSC-derived neuronal networks have developed and interconnected in a 3D environment shaped by vertically stacked scaffold layers. The iPSC-derived neuronal progenitor cells could develop into cortical projection neurons (CNPs) of all six layers, different types of inhibitory neurons and glia. The network showed strong neuronal spontaneous activity that combined individual and collective signaling events. Our results highlight advanced microstructured 3D scaffolds as a reliable platform for 3D in vitro modelling of neuronal functions.
Keywords: Scaffolds; neural models; two-photon polymerisation; human induced pluripotent cells